A NEW APPROXIMATION FOR INVENTORY CONTROL SYSTEM WITH DECISION VARIABLE LEAD-TIME AND STOCHASTIC DEMAND - Akcan, Serap (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Demand for any material in a hospital depends on a random arrival rate and random length of stay in units. Therefore, the demand for any material shows stochastic characteristics that make determining the optimum level of r and Q problem more difficult. Thus, in this study, a single item inventory system for healthcare was developed using a continuous review (r, Q) policy. A simulation meta-model was constructed to obtain equations for the average on-hand inventory and average number of orders per year. Then, the equations were used to determine the optimal levels of r and Q while minimizing the total cost in an integer non-linear model. The same problem investigated in this study was also solved using OptQuest optimization software.